IMPACT OF ARMED CONFLICT ON TOURISM IN KASHMIR - PEER AMIR AHMAD (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Many countries around the world rely heavily on tourism to support their economies. According to legend, Kashmir is known around the world as "The Paradise on Earth," because of its breath-taking beauty. Kashmir's natural beauty and rich cultural heritage are unrivalled anywhere on the planet. Every traveller fantasises about seeing Kashmir's lush green meadows, bubbling streams, and lily-covered lakes. Due to the on-going armed conflict that began in the early 1990s, this tourist destination has lost its appeal. When the tourism industry nearly collapsed in 1991, it had a significant impact on the entire state's economy, as well as individual households. Hundreds of thousands of people have died as a result of the chaos. Not only have precious lives been lost in Jammu and Kashmir, but the state's economy has also suffered a significant setback. Jammu and Kashmir has been undergoing political turmoil for the past 25 years. The tourism industry, without a doubt, has been hit the hardest by the on-going social and political unrest. The tourism industry has been hit just as hard as the allied industries, particularly Kashmiri art and craft. The present paper attempts to empirically study the impact of armed conflict on Kashmir's tourism. This supports the results, which were interpreted by the graphical representation.